Pathos dalam Dakwah Nazriel Abdul Muluk di Youtube - Sindi Sutiana; Supriyadi Supriyadi (UIR Press, 2023)
This research examines pathos in the form of three da'wah videos downloaded from YouTube in 2022. The informants in this study were Nazriel Abdul Muluk., Lc. While the problems that will be discussed in this study: (1) how is the pathos of feelings, emotions, hopes, hatred and affection in Nazriel Abdul Muluk's preaching. This study aims to describe, analyze, interpret and conclude the pathos of feelings, emotions, hopes, hatred, and compassion in Nazril Abdul Muluk's preaching on YouTube. This type of research is qualitative research with qualitative descriptive methods. Data collection techniques in this study using documentation techniques, analysis techniques, data reduction, and data presentation. The results of this study found that there were 25 data including pathos in the form of 2 data of touching feelings, 10 data of emotions, 4 data of hope, 3 data of hatred and 6 data of affection. So it can be concluded that the pathos used by Nazriel Abdul Muluk is more dominant in using pathos in the form of emotional touch to influence listeners to be able to understand what the speaker is conveying.